2010
DOI: 10.1177/1076029609360527
|View full text |Cite
|
Sign up to set email alerts
|

Coinheritance of Severe von Willebrand Disease With Glanzmann Thrombasthenia

Abstract: A 35-years old male patient presented severe bleeding was diagnosed to have type 3 von Willebrand disease (VWD) and carrier for Glanzmann thrombasthenia (GT). Propositus and family members were studied through basic coagulation tests and genomic DNA analysis. Two offspring of the family were diagnosed to have GT through platelet aggregation along with VWD carrier. The patient with VWD was found positive for homozygous truncating mutation R1659X in VWF gene, and all offspring were heterozygous carriers of null … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 12 publications
0
3
0
Order By: Relevance
“…Glanzmann's thrombasthenia and type 2N VWD Pontara et al 403 between Glanzmann's thrombasthenia and VWD has already been reported, taking into account that VWD is the most common inherited bleeding disorder [18,19], which involved quantitative VWF defects (type 1 and type 3 VWD).…”
Section: Discussionmentioning
confidence: 89%
“…Glanzmann's thrombasthenia and type 2N VWD Pontara et al 403 between Glanzmann's thrombasthenia and VWD has already been reported, taking into account that VWD is the most common inherited bleeding disorder [18,19], which involved quantitative VWF defects (type 1 and type 3 VWD).…”
Section: Discussionmentioning
confidence: 89%
“…For instance, rare coinheritance of GT with other bleeding disorders has been reported. 62 To ensure only families with true lack of segregation ($2 affected family members with at least 1 affected individual not carrying the variant of interest) are included, the PD-EP specifies that all affected family members must be well documented as having GT based on both bleeding phenotype and appropriate laboratory values (meeting the PP4_moderate criterion).…”
Section: Segregation Datamentioning
confidence: 99%
“…However, excluding the forms for which a candidate gene is known, the identification of new genetic defects underlying an IPFD is challenging and made particularly difficult by the complexity of the mechanisms regulating platelet activation, with many proteins not yet known to be involved in platelet function. Moreover, platelet disorders are heterogeneous and sometimes are coinherited with other genetic defects, such as the association of VWD and Glanzmann thrombasthenia, 18,52 or VWD and heterozygous mutations in platelet proteins (P2Y 12 , TP, and GPVI). 19 Finally, complex genetic conditions such as compound heterozygosity, large chromosome deletions (del11q23-ter in Paris Trousseau syndrome), and compound inheritance of a null allele and one point mutation (the 1q21.1 deletion associated with a point mutation in RBM8A described in thrombocytopenia absent radii 53 ), render the unraveling of an underlying genetic defect particularly complex.…”
Section: Genetic Testingmentioning
confidence: 99%